4CPS-067 Assessment of the effectiveness of using vancomycin in patients undergoing haemodyalisis - Torres, MI Sierra (Eur J Hosp Pharm, 2018)
BACKGROUND: Vancomycin is used commonly to treat Gram +bacteraemia in haemodialysis patients. The most accurate and practical method to monitor vancomycin effectiveness is to measure the trough vancomycin concentration. PURPOSE: To assess the effectiveness of treating with vancomycin in patients undergoing haemodialysis and the effectiveness of the interventions by the pharmacy service to reach the target concentration MATERIAL AND METHODS: Prospective, analytical study conducted between October 2013 and March2017. All patients in haemodialysis treated with vancomycin that had been monitored by the Pharmacy Service were included. The variables collected were: age, sex, weight, diagnosis, residual renal function, type of infection, microorganisms isolated, type of dialysis membrane, target level, loading dose, recommended dose, range of valleys, effectiveness of treatment (clinical and microbiological) and toxicity. The target serum concentration was between 15 and 20 µg/ml in severe infections and 10 and 15 µg/ml in milder cases. RESULTS: Fifty-eight patients with 65 episodes of treatment were included. 31 males and 27 females, with an average age of 63.5 years (27–91)±13.12 and weight of 73.1 kg 835–110)±13.97. Fifty-four (n=31) did not have residual renal function. 69.2% required specific treatment and 30.8% empirical. 58.5% of episodes used vancomycin to treat bacteraemias related to haemodialysis catheters. In 50.7% of episodes, high-flow membrane was used and low flux was used in 47.7%. In one case this data was unavailable. Eighty-three per cent of episodes had 15 to 20 µg/ml as their target level. Theaverage loading dose was 18.89 mg/kg (10–28.57)±3.65. Recommended doses varied.between 0 to 2 g. The target level was reached in 78.5% of episodes (n=51). The infection was cleared in 75% of episodes (n=49). Microbiological effectiveness was reached in 51% of cases (n=33). No adverse effect was detected. CONCLUSION: The infection was cleared in 75% of cases, and target concentration was reached in 78.5% of them, highlighting the need for monitoring by the pharmacy service. These results could help, with a further thorough study, to develop a clinical guide specific for these patients. No conflict of interest